2015
DOI: 10.1038/srep16024
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine regulates mTOR signalling in a region-dependent manner in depression-like mice

Abstract: Previous studies have demonstrated that the mammalian target of rapamycin (mTOR) signaling pathway has an important role in ketamine-induced, rapid antidepressant effects despite the acute administration of fluoxetine not affecting mTOR phosphorylation in the brain. However, the effects of long-term fluoxetine treatment on mTOR modulation have not been assessed to date. In the present study, we examined whether fluoxetine, a type of commonly used antidepressant agent, alters mTOR signaling following chronic ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 34 publications
7
44
0
Order By: Relevance
“…In contrast to the rapid effects of these agents, incubation with the typical monoaminergic antidepressants fluoxetine and desipramine for 1 hr did not influence phospho-ERK and phospho-S6K, demonstrating specificity of this signaling to the rapid acting antidepressants within this short timeframe. This is consistent with previous studies demonstrating that acute or chronic administration of fluoxetine or imipramine has no effect mTORC1 signaling in PFC (Li et al, 2010; Liu et al, 2015), although chronic fluoxetine administration reverses the down-regulation of mTORC1 signaling in mice exposed to chronic stress (Liu et al, 2015). Primary neuronal culture studies also report no effect of fluoxetine or imipramine on mTORC1 signaling, although incubation with high doses of escitalopram and paroxetine for 4 days reversed the down regulation of mTORC1 signaling caused by incubation with B27 depleted media (Park et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to the rapid effects of these agents, incubation with the typical monoaminergic antidepressants fluoxetine and desipramine for 1 hr did not influence phospho-ERK and phospho-S6K, demonstrating specificity of this signaling to the rapid acting antidepressants within this short timeframe. This is consistent with previous studies demonstrating that acute or chronic administration of fluoxetine or imipramine has no effect mTORC1 signaling in PFC (Li et al, 2010; Liu et al, 2015), although chronic fluoxetine administration reverses the down-regulation of mTORC1 signaling in mice exposed to chronic stress (Liu et al, 2015). Primary neuronal culture studies also report no effect of fluoxetine or imipramine on mTORC1 signaling, although incubation with high doses of escitalopram and paroxetine for 4 days reversed the down regulation of mTORC1 signaling caused by incubation with B27 depleted media (Park et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…A previous study reported that restraint stress tended to decrease the expression of SYP in the rat hippocampus, although this was restored to pre-stress levels after 2 weeks of treatment with venlafaxine (2). The present results revealed that CUMS caused a significant reduction in PSD 95 and SYP expression in the hippocampus, which was consistent with a previous study (26). Administration of Baf A1 for 4 weeks significantly increased the expression levels of SYP and PSD 95 in the CUMS group.…”
Section: Discussionsupporting
confidence: 92%
“…It was reported that both the immediate and long-term administration of fluoxetine has no effect on mTOR signaling in the PFC, although the chronic administration of fluoxetine reverses the downregulation of mTOR signaling in the hippocampus, but not in the PFC, of mice exposed to chronic stress (55). In the current study, we found that rapamycin and AZD8055 blocked the antidepressant effects of (S)-ketamine in a CSDS model, suggesting that mTOR signaling plays a role in the antidepressant effects of (S)-ketamine.…”
Section: Discussionmentioning
confidence: 99%